Pertanggungjawaban Pidana Anak Dalam Sistem Peradilan Pidana Anak Di Indonesia - Kristianto Jansen Hengkengbala (Lembaga Pengembangan Kinerja Dosen, 2023)
The aim of this research is to explore how Law Number 11 of 2012 regulates the Juvenile Criminal Justice System and how juvenile criminal responsibility is regulated in the juvenile criminal justice system in Indonesia. By applying normative juridical research methods, it can be concluded as follows: 1. The Juvenile Criminal Justice System aims to achieve practical progress in efforts to optimally protect children, who are considered valuable assets for the future of the nation and state. Legal protection for children is defined as legal protection measures for various freedoms and human rights of children, as well as interests related to their welfare. 2. Criminal liability for minors who are involved in violating the law in accordance with the provisions regulated in the Criminal Code and Law no. 11 of 2012 concerning the Juvenile Criminal Justice System. Children who are involved in criminal acts can still be held accountable, subject to criminal threats determined by the Criminal Code. The penalty for children is set at half the maximum penalty imposed on adults. It is important to note that life sentences and the death penalty are not applied to children in this context